Inhibition of CD44 induces apoptosis, inflammation, and matrix metalloproteinase expression in tendinopathy - Wu, Po-Ting (J Biol Chem, 2019)
Apoptosis has emerged as a primary cause of tendinopathy. CD44 signaling pathways exert anti-apoptotic and -inflammatory effects on tumor cells, chondrocytes, and fibroblast-like synoviocytes. The aim of this study was to examine the association among CD44, apoptosis, and inflammation in tendinopathy. Expression of CD44 and apoptotic cell numbers in tendon tissue from patients with long head of biceps (LHB) tendinopathy were determined according to the histological grades of tendinopathy. Primary tenocytes from Achilles tendon of Sprague–Dawley rats 1 week after collagenase injection were cultured with an antagonizing antibody against CD44. Treatment responses were determined by evaluating cell viability and expression of tendon-related proliferation markers, inflammatory mediators, and apoptosis. The expression of CD44 and apoptosis were positively correlated with the severity of tendinopathy in the human LHB tendinopathy. Furthermore, CD44 expression and apoptotic cells were co-stained in tendinopathic tendon. Blocking the CD44 signaling pathways in rat primary tenocytes by OX-50 induced cell apoptosis and the elevated levels of cleaved caspase-3. Furthermore, they had decreased cell viability and expression of collagen type I, type III, tenomodulin, and phosphorylated AKT. In contrast, there were elevated levels of inflammatory mediators, including interleukin (IL)-1β, IL-6, tumor necrosis factor-α, cyclooxygenase-2, and phosphorylated NF-κB, as well as matrix metalloproteinase (MMP) family members including MMP-1, -3, -9, and -13 in tenocytes upon OX-50 treatment. This study is the first to demonstrate the association of CD44 and apoptosis in tendinopathy. Our data imply that CD44 may play a role in tendinopathy via regulating apoptosis, inflammation, and extracellular matrix homeostasis.